The Social Integration of Urban Green Infrastructure Programmes in Land-Use Management Planning Practices in Stellenbosch Municipality - Van Harte, Kauthar (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.